Temperature distribution simulation and thermal properties investigation of hollow slab beam based on meteorological data - Zeng, Guosheng S; Song, Jun; Zhu, Chaoyu Y (Frontiers in Energy Research, 2022)
Natural environment has a great impact on the performance of bridge structures, such as the ambient temperature, solar radiation, climate extremes and so on. Due to the lack of regional pertinence in the provisions of the existing specifications on the temperature load standard, and the lack of verification of its adaptability of hollow slab beam bridge in the reconstruction and expansion project, it is necessary to study the temperature load of the beam based on the temperature data of the area where the bridge site is located. Based on the measured meteorological data, the cross-section temperature distribution characteristics of the hollow slab beam and the temperature load effect were investigated. The vertical temperature load model of the short and medium-span hollow slab beam was proposed according to the simplified temperature curve. Firstly, based on the annual measured meteorological data, the plane model was established to analyze the temperature distribution characteristics of the hollow slab beam. Secondly, according to the temperature field distribution of the beam cross-section, the solid model of 16 m hollow slab beam was established to analyze the distribution of the temperature load effect. Finally, based on the preliminarily proposed temperature curve, vertical temperature load models were proposed by introducing the theory of extreme value extrapolation. The studies have shown that the temperature of the hollow slab beam is approximately horizontal distributed, and temperature extreme value appear at the location of the beam web. The roof and floor of the hollow slab beam are compressed and the webs are tensioned in the positive temperature difference state, the stress condition is opposite under the negative temperature difference state. The positive and negative temperature load models can meet the extrapolation requirements of the bridge design reference period. This study innovatively proposed a temperature load model based on the temperature curve corresponding to the most unfavorable effect of the beam. The extrapolation idea in the derivation of vehicle load model is introduced as well. And a temperature load model suitable for the extension of hollow slab bridges in Guangdong is established in this study.